GLA Gene Mutation in Hypertrophic Cardiomyopathy with a New Variant Description: Is it Fabry's Disease? - Chaves-Markman,Ândrea Virgínia (2019)
Abstract Background: Fabry disease (FD) is an X-linked lysosomal storage disorder caused by mutations in the alpha galactosidase A gene (GLA) that lead to the enzymatic deficiency of alpha galactosidase (α-Gal A), resulting in the accumulation of globotriaosylceramide (Gb3) and globotriaosylsphingosine (lyso-Gb3), causing multiple organ dysfunctions. Objective: To perform GLA gene screening in a group of patients with echocardiographic diagnosis of hypertrophic cardiomyopathy (HCM). Methods: a cross-sectional study was conducted with HCM patients from a university hospital. Patients with coronary artery disease and valvulopathies were excluded. Mutation analysis of the GLA gene was performed. In male subjects, the analysis was performed after evidence of low α-Gal A activity. Results: 60 patients with echocardiographic diagnosis of HCM were included. Age ranged from 12 to 85 years and 60% were women. Mean myocardial fibrosis percentage on MRI was 10.7 ± 13.1% and mean ventricular thickness was18.7 ± 6.7 mm. Four patients had the following GLA gene mutations: c.967C>A (p.Pro323Thr), not yet described in the literature; c.937G>T (p.Asp313Tyr); and c.352C>T (p.Arg118Cys). All patients had normal levels of lyso-Gb3 and non-ischemic myocardial fibrosis on magnetic resonance imaging; one patient had proteinuria and one patient had ventricular tachycardia. Conclusion: in this study, the frequency of mutation in the GLA gene in patients with HCM was 6.7%. A novel mutation in exon 6 of the GLA gene, c.967C>A (p.Pro323Thr), was identified. Patients with HCM may have GLA mutations and FD should be ruled out. Plasma (lyso-Gb3) levels do not seem to be sufficient to attain a diagnosis and organ biopsy should be considered.